Persepsi Mahasiswa tentang Peranan Perkuliahan Pedagogik Kejuruan dan Metoda Mengajar Khusus terhadap Kesiapan Mengajar - Renika Br Sipahutar; Hambali Hambali (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to determine how students' perceptions of the role of Vocational Pedagogics and Metoda Mengajar Khusus (MMK) lectures on student teaching readiness. This type of research is descriptive quantitative research. The research population is the 2018 Electrical Engineering Education Study Program students who have passed the Vocational Pedagogics, Metoda Mengajar Khusus, and Program Pengalaman Lapangan Kependidikan (PPLK) courses, totaling 55 students. The sampling technique in this study was total sampling, meaning that the entire population was used as the research sample, namely 55 people. The instrument used in this research is a questionnaire with the provision of answers always, often, sometimes, rarely, and never. Based on the results of the study, the descriptive analysis obtained the average value of the respondent's level of achievement (TCR) for each indicator in the questionnaire was classified as good. This shows that the mean score of the dominant respondents' answers is high so that the TCR number can be obtained. Furthermore, the inductive analysis obtained the results of hypothesis testing that students' perceptions of the role of the Vocational Pedagogic course (X1) and the Metoda Mengajar Khusus course (X2) partially and simultaneously have a positive and significant influence on teaching readiness (Y).